A Local-Content Based Comic: A Fun Media on Teaching Reading in New Normal Era - Miftahul Jannah; Humairah Humairah; Ilham Ilham; Iskandar Iskandar (Universitas Cokroaminoto Palopo, 2021)
Owing to the restrictions on the time of face-to-face lessons, a new teaching method has been created under the new normal. The teachers must be so innovative in choosing appropriate media as well as maintaining students’ mood in learning. This literature study aims at showing another choice of media that teachers may have in teaching English reading during the pandemic era. A comic with local content based emerge as a fun medium for teaching and learning reading English during the pandemic era. The visuals help improve students comprehension on the text as they provide “additional contextual information” which is in line with DCT (Dual Code Theory). Moreover, the use of local content based stories contributed to the high effect of cultural schema on comprehension.